2020
DOI: 10.1016/j.bja.2020.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating intubation boxes for airway management

Abstract: home-made aids, however well intentioned. We must protect our staff during high-risk procedures, but not when this confers a threat to patient safety. Whilst both the safety and efficacy of barrier enclosures in airway management remain unproved, our focus should continue to be on the use of appropriate and well-fitted personal protective equipment, worn and disposed of effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 5 publications
0
30
1
2
Order By: Relevance
“…Actual efficacy is not assessed in this report. Hill and colleagues 47 Original article Technical description CPS over customised frame Preliminary use in 25 patients No patient information given; 25 cases in emergency department ‘Corona Curtain’ barrier Use described as simple, pragmatic, and cost effective Alves Filho and colleagues 48 Original article Technical description CPS + frame N/A N/A Polyethylene sheet on metallic frame used for tracheostomy (sterile) Fully autoclavable; free movement inside; incomplete barrier; concerns for correct removal Gore and colleagues 49 Original article Simulation study Acrylic panels + CPS Four mannequin simulations Intubation using four methods (including control) using a mannequin model with smoke generator Acrylic panels supplemented by CPS in simulation study with mannequin Reduced aerosol dispersion with acrylic panels combined with CPS than with panels or no barrier Kinjo and colleagues 50 Research letter Clinical report Metal brackets + acrylic panel One patient Intubation/extubation with barrier enclosure of COVID suspected patient Application of novel barrier-enclosure system More economic and easy access than AB; care for metal parts contact Dalli and colleagues 51 Research letter Simulation study AB One Simulated OT setting with coughing human volunteer, detection of airflows (assumption that airflows carry droplets/aerosols); schlieren imaging of airflows around the AB during both normal and deep exhalation and during coughing to assess aerosol spreading High-speed imaging to assess airflows inside/outside the AB AB does not contain airflows; visualised airflows also from side ports; concerns for added complexity and secondary aerosolisation during doffing/cleaning Matava and colleagues 52 Guidelines Guidelines for paediatric airway management in COVID-19 patients CPS N/A (paediatric) N/A Discussion of barrier systems on anaesthetic equipment and on patient's airway devices The PeDI-C recommended a transparent barrier over the airway device and patient's hea...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actual efficacy is not assessed in this report. Hill and colleagues 47 Original article Technical description CPS over customised frame Preliminary use in 25 patients No patient information given; 25 cases in emergency department ‘Corona Curtain’ barrier Use described as simple, pragmatic, and cost effective Alves Filho and colleagues 48 Original article Technical description CPS + frame N/A N/A Polyethylene sheet on metallic frame used for tracheostomy (sterile) Fully autoclavable; free movement inside; incomplete barrier; concerns for correct removal Gore and colleagues 49 Original article Simulation study Acrylic panels + CPS Four mannequin simulations Intubation using four methods (including control) using a mannequin model with smoke generator Acrylic panels supplemented by CPS in simulation study with mannequin Reduced aerosol dispersion with acrylic panels combined with CPS than with panels or no barrier Kinjo and colleagues 50 Research letter Clinical report Metal brackets + acrylic panel One patient Intubation/extubation with barrier enclosure of COVID suspected patient Application of novel barrier-enclosure system More economic and easy access than AB; care for metal parts contact Dalli and colleagues 51 Research letter Simulation study AB One Simulated OT setting with coughing human volunteer, detection of airflows (assumption that airflows carry droplets/aerosols); schlieren imaging of airflows around the AB during both normal and deep exhalation and during coughing to assess aerosol spreading High-speed imaging to assess airflows inside/outside the AB AB does not contain airflows; visualised airflows also from side ports; concerns for added complexity and secondary aerosolisation during doffing/cleaning Matava and colleagues 52 Guidelines Guidelines for paediatric airway management in COVID-19 patients CPS N/A (paediatric) N/A Discussion of barrier systems on anaesthetic equipment and on patient's airway devices The PeDI-C recommended a transparent barrier over the airway device and patient's hea...…”
Section: Resultsmentioning
confidence: 99%
“…All were published between December 1, 2019 and May 27, 2020. There were 19 correspondences, 4e22 16 letters to the editor, 23e33,35e39 10 original articles, 40e49 three research letters, 34,50,51 one guideline, 52 one short recommendation, 53 one case report, 54 and one quality improvement study. 55 Of these reports, there were only six case reports or small case series.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…A potential disadvantage of the box is the restriction to movement and adapting to a new way of intubation. 6 In the event that the airway proves to be difficult, the box should be immediately abandoned.…”
mentioning
confidence: 99%
“…Simulations have demonstrated that without the use of a barrier, simulated droplets and aerosols can be found on the gown, gloves, face mask, eye shield, hair, neck, ears, and shoes of the intubater [ 4 - 6 ]. Some have utilized a plastic intubation box while others have utilized a clear plastic drape over a patient’s head during intubation and extubation in order to prevent respiratory droplets and aerosols from spreading [ 4 , 5 , 7 ]. These barriers have shown reduced contamination to the area around the patient in simulation [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%